The presentation of childhood obsessive-compulsive disorder across home and school settings - A preliminary report - SABUNCUOĞLU, OSMAN TALAT (SAGE PUBLICATIONS LTD, 2006)
This study aimed to determine the exact pattern of obsessive-compulsive disorder (OCD) symptoms in children displayed across school and home settings. Twenty-six school children (aged 7 through 17) with OCD were tested using the Children's Yale-Brown Obsessive Compulsive Scale (CY-BOCS), the Clinical Global Impression (CGI) - severity subscale and a questionnaire which consists of items serving to compare the symptoms between home and school settings. The mean obsession and compulsion subscores on the CY-BOCS were found to be 10.73 +/- 3.14 and 10.88 +/- 3.17, respectively, both summing up a Total score of 21.61 +/- 5.52. The mean CGI-severity scores, rated for home and school settings were 4.42 +/- 0.90 and 2.42 +/- 1.13 respectively, indicating a strong difference in the presentation of OCD between those settings (t = 7.02, df = 50, p < 0.0001). No gender, diagnosis (pure versus comorbid) and age effect (7 to <= 12 years versus > 12 to 17 years) was found on the CY-BOCS and CGI-severity subscale (Mann-Whitney U test, all p > 0.05). The presentation difference we have noted in this study is a significant finding. Further studies are needed to delineate the characteristics of this phenomenon with possible implications for diagnosis, management and treatment.
Keywords: child; obsessive-compulsive disorder; schools; FUNCTIONAL IMPAIRMENT; CHILDREN; ADOLESCENTS